SRPK1 regulates RNA binding in a pre‐spliceosomal complex using a catalytic bypass mechanism. (2nd July 2022) - Aubol, Brandon E.; Adams, Joseph A.
Abstract : Serine‐arginine protein kinase 1 (SRPK1) phosphorylates serine‐arginine (SR) proteins in the cytoplasm, directing them to the nucleus for splicing function. SRPK1 has also been detected in the nucleus but its function here is still not fully understood. We now demonstrate that nuclear SRPK1 can regulate U1‐70K, a protein component of the uridine‐rich 1 small nuclear ribonucleoprotein (U1 snRNP) that binds SR proteins and facilitates 5′ splice‐site selection in precursor mRNA. We found that SRPK1 uses a large, disordered domain to bind U1‐70K, regulating the interaction of an exonic splicing enhancer (ESE) to the associated SR protein. Surprisingly, the catalytic activity of SRPK1 is not required for this phenomenon. Instead, SRPK1 associates directly with the N‐terminus of U1‐70K and alters the regulatory function of the distal C‐terminus, modifying interactions between the U1‐70K:SR protein complex and the ESE. Disruption of SRPK1 binding to this complex affects the alternative splicing of genes modulated by the C‐terminus of U1‐70K. Such findings suggest that, in addition to operating as a traditional serine‐modifying catalyst, SRPK1 can also bypass this intrinsic activity to regulate RNA contacts in an early pre‐spliceosomal complex. Abstract : The 5' splice site in precursor mRNA is initially recognized by U1 snRNP (small nuclear ribonucleoprotein). This interaction is facilitated by phosphorylation‐dependent interactions between U1‐70K in U1 snRNP and members of the serine‐arginine (SR) protein family, which bind upstream RNA sequences in exons. Here, Aubol and Adams show that the serine‐arginine protein kinase SRPK1 uses a disordered region to bind U1 snRNP and modulate RNA interactions by inducing conformational changes across U1‐70K in an activity‐independent manner. This work unveils a previously unknown role of nuclear SRPK1 as a non‐catalytic, structural regulator of RNA interactions in an early pre‐spliceosomal protein complex.